Effect of the porous stainless steel substrate shape on the ZrO 2 deposition by vacuum assisted dip-coating - Contardi, Ignacio (2017)
The effect of the support shape on the deposition of ZrO2 by the vacuum-assisted dip-coating method was studied. Disc-shaped and tubular porous stainless steel substrates were used to obtain ZrO2 coated supports for the synthesis of PdAu alloy composite membranes. The microstructure of the ZrO2 modified supports was evaluated by scanning electron microscopy and confocal laser microscopy. Besides, a qualitative assessment of the porosity and roughness of the porous substrates was performed by confocal laser microscopy. Dense and continuous palladium-alloy films were deposited on top of the modified tubes after thirteen ZrO2 deposition-calcination cycles. Cross-section EDS mapping and XRD diffraction analysis showed that a complete PdAu alloy formation was obtained even after annealing at 723 K in hydrogen stream during 5 days.